SYNTHESIS, CHARACTERIZATION AND AMELIORATING EFFECT OF QUERCETIN NANOPARTICLES AGAINST ETHION-INDUCED OXIDATIVE STRESS IN MALE RATS - Ranjith D; Dhaval J Kamothi; Madhu CL; Padhi PK; Dinesh Kumar; Telang AG (Exploratory Animal and Medical Research, 2023)
Pesticides are the ubiquitous xenobiotics. Ethion, an organophosphorus pesticide, induces adverse effects in animals upon ingestion. Quercetin, a potent antioxidant, has very low water solubility. As a result, this study aimed to synthesize and analyze nanoparticles of quercetin and assess their potential to mitigate oxidative harm caused by ethion in rats. Ethion was administered at dose rates of 3.6 and 7.2 mg/kg once daily for 90 days. Quercetin (50 mg/kg) and quercetin nanoparticles (50 mg/kg) were also simultaneously administered to high-dose ethion-administered rats in separate groups for 90 days. A 10% blood hemolysate was prepared and analyzed for different biochemical parameters. Groups subjected to ethion treatment exhibited a notable increase in lipid peroxidation, indicated by heightened MDA production, alongside a significant reduction in SOD levels, Catalase, GSH, GPX, GST, and GR. In groups treated with quercetin and quercetin nanoparticles, the impact of ethion-induced oxidative stress was notably mitigated, particularly in the quercetin nanoparticles-treated group.